2013
DOI: 10.1002/er.3009
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich gas production from ethanol steam-reforming reaction using NiZr-loaded MCM-48 catalysts at mild temperature

Abstract: SUMMARY The rich‐hydrogen generation from ethanol steam reforming over NiZr, which is used as an anode material in solid oxide fuel cells, ‐loaded MCM‐48 (NiZr/MCM‐48) catalyst was investigated in this study. We used an impregnation approach to synthesize an MCM‐48 (70.0 wt‐%) support loaded with bimetallic NiZr (30.0‐wt%, Ni:Zr atomic ratio = 4:6, 5:5, and 6:4), and the prepared catalysts were applied to the steam‐reforming reactions of ethanol. These three bimetallic NiZr/MCM‐48 catalysts exhibited significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These results indicated that Al-MCM-48 had good activity and stability for the transalkylation of DIPB with benzene and its activity and stability increased at high Si/Al ratios. It is widely accepted that the accessibility of catalytic active sites plays a critical role in some diffusion-controlled reactions [10]. As has been reported and confirmed in previous studies, the available active sites in the mesoporous materials are effectively utilized.…”
Section: Resultssupporting
confidence: 51%
“…These results indicated that Al-MCM-48 had good activity and stability for the transalkylation of DIPB with benzene and its activity and stability increased at high Si/Al ratios. It is widely accepted that the accessibility of catalytic active sites plays a critical role in some diffusion-controlled reactions [10]. As has been reported and confirmed in previous studies, the available active sites in the mesoporous materials are effectively utilized.…”
Section: Resultssupporting
confidence: 51%
“…Most ethanol SR (ESR) studies evaluated nickel-based catalysts supported on Al 2 O 3 , SiO 2 , and various zeolites containing alkali metals [9,10]. On the other hand, the Ni-based Al 2 O 3 support catalysts are susceptible to deactivation, resulting from carbon deposition, even when operating at steam-to-carbon ratios predicted to be thermodynamically outside of the carbon-forming regime.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other possible hydrogen source in liquid form, such as methanol or dimethyl ether, ethanol is not only easier to handle, store, and transport, but also has lower toxicity and volatility. Therefore, this high energy density compound is a key candidate for hydrogen production .…”
Section: Introductionmentioning
confidence: 99%
“…There are three different catalytic routes that can be used to convert ethanol into hydrogen, i.e. steam reforming , partial oxidation , and oxidative steam reforming , which combine steam reforming and partial oxidation. On the other hand, hydrogen can also be generated by the other methods such as photocatalytic reaction with modified TiO 2 , water gas shift reaction of synthesis gas , and reaction with sodium borohydride solution .…”
Section: Introductionmentioning
confidence: 99%